Impact of sex on the outcome of troponin-positive patients with non-obstructive coronary arteries - Fabienne Kreimer; Clara Schlettert; Mohammad Abumayyaleh; Ibrahim Akin; Mido Max Hijazi; Michael Gotzmann; Nazha Hamdani; Andreas Mügge; Assem Aweimer; Ibrahim El-Battrawy (Scientific Reports)
Abstract The aim of this study was to investigate the prognostic impact of sex on in- and out-of-hospital adverse events in troponin-positive patients with non-obstructive coronary artery disease (CAD). 24,775 patients who underwent coronary angiography from 2010 to 2021 were screened for this study. The final study population consisted of 373 troponin-positive patients with non-obstructive CAD with a follow-up period of 6.2 ± 3.1 years, with 185 males and 188 females. The primary study end point was a composite of in-hospital adverse events. Secondary endpoints covered out-of-hospital adverse events during follow-up. In-hospital adverse event rates revealed no significant sex differences (37.8% in males vs. 33.0% in females). Significantly more long-term adverse events occurred in women compared with men during follow-up (27.3% vs. 41.9%). All-cause mortality was significantly higher in women than in men (29.7% vs. 21.2%, p = 0.022). Cox analysis identified age ≥ 70 years, arterial hypertension, diabetes mellitus, supraventricular tachycardia, pulmonary disease, neurological disease, and kidney disease as predictors of out-of-hospital adverse events, whereas male sex was associated with a better long-term outcome. While sex differences were not significant in in-hospital adverse events, females demonstrated a higher incidence of out-of-hospital adverse events and increased mortality during long-term follow-up compared to males.